2020
DOI: 10.1002/1878-0261.12698
|View full text |Cite
|
Sign up to set email alerts
|

RAF dimer inhibition enhances the antitumor activity of MEK inhibitors in K‐RAS mutant tumors

Abstract: The mutation of K-RAS represents one of the most frequent genetic alterations in cancer. Targeting of downstream effectors of RAS, including of MEK and ERK, has limited clinical success in cancer patients with K-RAS mutations. The reduced sensitivity of K-RAS-mutated cells to certain MEK inhibitors (MEKi) is associated with the feedback phosphorylation of MEK by C-RAF and with the reactivation of mitogen-activated protein kinase (MAPK) signaling. Here, we report that the RAF dimer inhibitors lifirafenib (BGB-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…3 C). As previously reported in studies using two-dimensional cell lines, phosphorylation of MEK was increased by MEK inhibition in a time-dependent manner 34 , 38 , 39 . Phosphorylation of MEK was shown to be induced by the allosteric inhibition of MEK in RAS-activated cells 34 .…”
Section: Resultssupporting
confidence: 78%
“…3 C). As previously reported in studies using two-dimensional cell lines, phosphorylation of MEK was increased by MEK inhibition in a time-dependent manner 34 , 38 , 39 . Phosphorylation of MEK was shown to be induced by the allosteric inhibition of MEK in RAS-activated cells 34 .…”
Section: Resultssupporting
confidence: 78%
“…For several type II RAF inhibitors, such as LY3009120, AZ-628, TAK-632, TAK-580, or lifirafenib, which have low apparent dissociation constants and a narrow range of paradoxical activation, synergy with MEK inhibitors has been observed ( Yen et al, 2018 ; Yuan et al, 2020 ). However, our calculations suggest that the zone where antagonism prevails can still be substantial, and sufficiently high doses of type II RAF inhibitors are required to remain in the synergy zone ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in CRC cells, it has been demonstrated that KRAS mutations lead to aberrantly elevated MAPK signalling [ 15 , 16 ]. Therefore, many attempts have been made to target and inhibit molecules downstream of KRAS, although breakthrough success in therapeutic applications has not been realised [ 17 ].…”
Section: Mutant Kras-driven Enhanced Cell Signalling In Crcmentioning
confidence: 99%